Cooler than lemonade - Jerath, Harshita (Sourcebooks Jabberwocky, an imprint Sourcebooks Kids, 2023)
Eva starts a lemonade stand but competition from Jake's stand across the street creates a tough challenge so Eva decides to make kulfi, her own Indian ice cream, and partner with Jake. Includes recipe.